How real is real enough? Participant feedback on a behavioral simulation used for information-seeking behavior research. (March 2023) - Buhler, Amy G.; Brannon, Brittany; Cataldo, Tara Tobin; Faniel, Ixchel M.; Connaway, Lynn Silipigni; Valenza, Joyce Kasman; Elrod, Rachael; Cyr, Christopher
A challenge of studying information-seeking behavior in open web systems is the unpredictability of those systems. One solution to counteract this issue is employing a simulation to ensure experimental control. However, concerns arise over the realism of such an environment. This paper assesses the realism of a behavioral simulation used to study the evaluation behavior of 175 students from fourth grade through graduate school. We assess realism through the examination of targeted participant feedback about what would have made the simulated environment and tasks more realistic to these participants. Based on this feedback, we reflect on decisions made in designing the simulation and offer recommendations for future studies interested in incorporating behavioral simulation in their research design. We find that a thoughtfully designed simulation can elicit naturalistic behavior when the controlled environment is designed to be realistic in meaningful ways. Because the simulation does not have to perfectly match reality to elicit these behaviors, designing a simulation that is real enough is an effective method to study information-seeking behavior.